MODEL CLIS (CHILDREN LEARNING IN SCIENCE) ON SCIENCE PROCESS SKILL ON HEAT TRANSFER MATERIAL - Rekha Putri Apriliani; Mirna Alvia; Rina Agustin Jatnika; Restu Lesmana; Galih Dani Septiyan Rahayu (COLLASE (Creative of Learning Students Elementary Education), 2018)
Articles should include abstracts of 200 words or less. The abstract should not repeat the information already in the title. The abstract should be written in English and Indonesian. The typeface used Times New Roman 11 point. The abstract should be clear, descriptive and should provide a brief overview of the problem under study. Abstracts include reasons for choosing topics or the importance of research topics, research methods and outcome summary. The abstract should end with a comment about the importance of a brief outcome or conclusion.